(untitled) (Current Horticulture, 2024)
India’s vegetable oil demand is growing at a faster pace and by 2030 it is expected to be around 34 million tonnes. Palm oil is the most viable option to meet the edible oil demand of the country. India is the only country which grows this crop under irrigated conditions because, it is a water-loving crop and is the only option to lessen the gap between vegetable oil demand and production in India. Its theoretical yield potential is up to 18 tonnes of oil per hectare. Till now, its potential has not been fully exploited in terms of FFB production as most of the farmers are new to this crop and also it requires judicious management of resources like water and nutrients. Further, FFB yield levels at present are highly variable in different states and there is a large scope for enhancing the productivity by adopting recommended management practices. If proper management is provided, its crop could do wonders with very good yields under irrigated conditions. For reaping higher economic benefits from this crop, oil palm farmers should resort to good management, intercropping, inclusion of other components of farming like cattle, goats and poultry etc. Farmers also have to be made aware of different options of waste utilization for productive purposes through value-addition. In addition, with good R&D support, right policy back up from GOI, the income of oil palm farmers is expected to grow rapidly while meeting the edible oil demand of the country. Oil palm was introduced to India during 1970s and at present it occupies nearly 0.316 million ha of area in our country. This is most suitable crop to meet the vegetable oil demands in our country, contributing very high oil yield on unit area basis. The Government of India is emphasizing its expansion even to non-traditional areas because of its high yield potential. At present, average fresh fruit bunch yields are around 4.3-6.1 tonnes/ha at national level. By adopting suitable practices detailed in this discussion, the yield levels could be improved substantially.